2011
DOI: 10.1016/j.ccr.2010.10.035
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Promotes Expansion of Breast Tumor Initiating Cells through Activation of RAF1-β-Catenin Signaling

Abstract: Summary It has been proposed that an aggressive secondary cancer stem cell population arises from a primary cancer stem cell population through acquisition of additional genetic mutations and drives cancer progression. Overexpression of Polycomb protein EZH2, essential in stem cell self-renewal, has been linked to breast cancer progression. However, critical mechanism linking increased EZH2 expression to BTIC (breast tumor initiating cell) regulation and cancer progression remains unclear. Here, we identify a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
340
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(357 citation statements)
references
References 48 publications
12
340
4
1
Order By: Relevance
“…Ectopic EZH2 expression increased the stem cell pool in nontumorigenic breast cells, whereas EZH2 down-regulation reduced the breast TIC population in vitro and in xenograft studies. Our data strengthen those from an earlier study showing that EZH2 can promote breast TIC expansion (13) and further demonstrate the consequences of EZH2 levels on breast cancer initiation. EZH2 down-regulation in TN breast cancer cells retarded breast cancer initiation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Ectopic EZH2 expression increased the stem cell pool in nontumorigenic breast cells, whereas EZH2 down-regulation reduced the breast TIC population in vitro and in xenograft studies. Our data strengthen those from an earlier study showing that EZH2 can promote breast TIC expansion (13) and further demonstrate the consequences of EZH2 levels on breast cancer initiation. EZH2 down-regulation in TN breast cancer cells retarded breast cancer initiation.…”
Section: Discussionsupporting
confidence: 81%
“…From a clinical perspective, blocking EZH2 may prevent or ameliorate breast cancer initiation in women with high EZH2 protein expression levels in their breast epithelium. Despite interest in the association between EZH2 functions, breast TICs, and TN breast cancer (13), the molecular mechanisms underlying the tumorigenic function of EZH2 in this cancer subtype and the relationship to NOTCH1 signaling have not yet been considered. Furthermore, whereas a role for NOTCH1 in breast tumorigenesis has been established in vivo (30), the factors regulating increased NOTCH1 expression and signaling in breast cancer cells are largely unknown (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further demonstrated that HIF1-α inhibited PRC2 activity through transcriptionally repressed PRC2 components, SUZ12 and EED, selectively. In contrast, HIF1-α was able to induce EZH2 mRNA expression, as is consistent with a previous report identifying hypoxic response element in EZH2 promoter (25). Of interest, a recent study has reported that PRC2/H3K27me3 inactivation induces HIF1A mRNA expression in multiple myeloma (54).…”
Section: Discussionsupporting
confidence: 56%
“…Intriguingly, HIF1-a inhibition on PRC2 does not affect Ezh2, which is consistent with the report of a positive transcriptional regulation of HIF1-a on EZH2 promoter. 6 These findings identified dual antagonistic roles of HIF1-a in determining the activity of Ezh2 in response to hypoxia, and thus the cellular signaling changes leading to aggressive TNBC development.…”
mentioning
confidence: 98%